Understanding the Antecedents of Knowledge Sharing Behavior From the Theory of Planned Behavior Model: Cross-Cultural Comparisons Between Mainland China and Malaysia - Yang, Min; Xu, Ping (Frontiers in Psychology, 2021)
Affected by the COVID-19, in addition to keeping away the impact of the pandemic on their business practices, many enterprises have proposed relevant measures to protect their employees' job safety and security. Especially for enterprises with high dependence on knowledge resources, employees' innovation and knowledge sharing play a vital role. In the context of global economic austerity, how to put forward the corresponding plan of knowledge sharing intention to improve the knowledge sharing behaviour of employees for enterprises is worth discussing. Mainland China and Malaysia have different quarantine policies and similar industrial structures. This study examines the awareness of Mainland China versus Malaysian employees, and evaluates the relationship among self-efficacy, job security, market orientation, knowledge sharing intention and knowledge sharing behaviour from the theory of planned behavior. In this study, a total of 627Mainland China and 434Malaysianparticipants were collected to compare both groups in development of employees’ knowledge sharing behaviour. In this study, a variance-based structural equation modeling (PLS-SEM) was performed to test the proposed hypothesizes and conduct comparative analysis. The results in both samples show that self-efficacy, job security and market orientation have positive and significant effects on knowledge sharing intention; self-efficacy has positive and significant effects on job security; knowledge sharing intention has positive and significant effects on knowledge sharing behaviour. Moreover, there are several significant differences between Mainland China and Malaysia in the examinations of path comparisons.